Chlamydia trachomatis: Management in Pregnancy. Issue 2 (1995) - Allaire, Alex; Nathan, Lawrence; Martens, Mark G.
Abstract : Chlamydia trachomatis is a sexually transmitted disease (STD) commonly diagnosed in pregnancy. C. trachomatis has been linked to several pregnancy complications including premature rupture of membranes (PROM), preterm labor and birth, low birth weight, intrauterine growth retardation, and postpartum endometritis. Infants born to mothers through an infected birth canal are at risk for acquiring C. trachomatis pneumonitis, conjunctivitis, and nasopharyngeal infection. The standard treatment of C. trachomatis in pregnancy is erythromycin. Recently, amoxicillin and clindamycin have been added as alternative regimens for those patients intolerant of erythromycin. This paper reviews the effectiveness and tolerance of the alternative regimens compared with erythromycin and the success of antepartum treatment of chlamydia in preventing the poor pregnancy outcome and neonatal morbidity associated with C. trachomatis.